Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Extracellular electron transfer by the cultured coral photosymbiont Symbiodinium microadriaticum - Loris Marcel; James T. Simon; Joshua M. Lawrence; Svetlana Menkin; Adrian C. Barbrook; R. Ellen R. Nisbet; Christopher J. Howe; Jenny Z. Zhang (Photosynthesis Research, 2026)
Photosynthetic microorganisms may show extracellular electron transfer (EET), in which some of the electrons generated by photosynthesis or respiration are lost from the cell. Most studies have focussed on cyanobacteria, with very few on eukaryotic algae. Here we demonstrate EET from the eukaryotic dinoflagellate alga Symbiodinium microadriaticum , a species that can form symbiosis with corals and other Cnidaria. We show that the EET involves diffusible electroactive species, which may represent a previously unsuspected route for communication between symbionts and hosts. We show that EET can be used to study photosynthetic and respiratory functions in the dinoflagellate. We also show that it can provide information on the effects of environmental stresses including changes in temperature (linked to coral bleaching), pH and light intensity. The electrochemical platform outlined in this study offers a novel tool for studying dinoflagellate physiology, the coral-dinoflagellate symbiosis, and the molecular mechanisms of bleaching.

Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Correspondence between stated and operational preferences – An examination of overall liking, preference rankings, and three methods of takeaway choice - Adam Chismar; Christopher T. Simons (Food Quality and Preference, 2026)

Carbon Fluxes of Contrasting Degraded Peatland Pilot Sites During Early-stage Restoration: Ex-milled Bare Peat and Grazed Grassland Conversion - Anna T. Keightley; Christopher D. Field; Michael Longden; Simon J. M. Caporn (Environmental Management, 2026)
The recovery of degraded peatlands can make significant contributions to reducing greenhouse gas emissions and climate warming. This study examines restoration techniques on shallow ex-milled peatland and intensively grazed pasture on deeper peat, both subject to prior drainage. Carbon greenhouse gases (GHGs) were monitored for 3 years following restoration treatment. After drainage-blocking measures, the ex-milled peatland was ‘companion planted’ with Eriophorum species and Sphagnum . The carbon balance was highly dependent on plant age and condition, with a high CO 2 equivalent (CO 2 e) uptake when plants were vigorously growing (year 1: −22.4 ± 32.9 t CO 2 e ha −1 yr −1 ), and high emission when plants were mature and in various stages of senescence (year 2: 26.1 ± 26.4 and year 3: 16.4 ± 9.7 t CO 2 e ha −1 yr −1 ). Bare peat controls had a mean emission of 6.21 ± 1.68 t CO 2 e ha −1 yr −1 over the study period. At the other site, the grazed pasture was stripped, the bare surface planted with Sphagnum plugs, and irrigation was intensively managed via bunding, ditches, and automatic water pumping. Carbon GHG emissions were significantly reduced on this ‘carbon farm’ (2.77 ± 0.95 t CO 2 e ha −1 yr −1 ) compared to a neighbouring drained, grazed pasture control (31.7 ± 10.3 t CO 2 e ha −1 yr −1 ) over the study period (mean ± SD throughout). It appears clear that the cyclical nature of Eriophorum plant growth may only deliver carbon benefits on shallow peat over the long term if groundwater levels can be adequately supported and if climatic conditions are favourable. Conversion of grazed pasture to wetter farming crops, such as Sphagnum , can potentially deliver immediate carbon benefits, although, in this pilot, any potential loss of CO 2 e due to degraded topsoil removal, creation of bunds and irrigation ditches was not accounted for.

Transforming food authenticity testing by the exploitation of a machine learning – Data fusion approach: a tea case study - Yicong Li; Natasha Logan; Awanwee Petchkongkaew; Yunhe Hong; Xiaotong Liu; Nicholas Birse; Simon Haughey; Terry F. McGrath; Di Wu; Christopher T. Elliott (Food Chemistry, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Portable NIR spectrometer and FTIR and soft modelling to authenticate edible cricket, mealworm and buffalo worm flour - J.P. Cruz-Tirado; Simon A. Haughey; Christopher T. Elliott; Douglas Fernandes Barbin (Food Control, 2026)

Two contrasting swamp forest succession pathways in central Congo Basin peatlands - Donna Hawthorne; Ian T. Lawson; Greta C. Dargie; Nicholas T. Girkin; Bart Crezee; William Hiles; George E. Biddulph; Yannick E. Bocko; Arnoud Boom; Corneille E.N. Ewango; Yannick Garcin; Pauline Gulliver; et al. (Quaternary Science Reviews, 2025)

Comparison of ratings based and choice based approaches at integrating sensory attributes with extrinsic product attributes - Samuel Hoffman; Guilherme Signorini; Christopher T. Simons (Food Research International, 2025)

Determination of Toxic Tropane Alkaloids in Globally Sourced Soya, Cereals and Products Using Dilute-and-Shoot Technique Coupled with LC-MS/MS - Rufielyn S. Gravador; Brett Greer; Simon A. Haughey; M. Mar Aparicio-Muriana; Wilfred A. Abia; Alexandra-Irina Mavrochefalos; Anne P. Nugent; Christopher T. Elliott (Exposure and Health, 2025)
For the first time, this study reports the content of tropane alkaloids (TAs) in soybean and soymeal samples sourced from 13 different countries, as well as in various cereals (including corn, millet, wheat, and sorghum) and a product (Super Cereals). The analysis was conducted using a fully validated solid-liquid extraction (SLE) with dilute-and-shoot (DnS) method along with a liquid chromatography-tandem mass spectrometry (LC-MS/MS) triple quadrupole system. The samples were extracted using a solution of acetonitrile and water (60:40) with 1% formic acid. The limits of quantification (LOQ) were 0.10 µg kg −1 and 0.25 µg kg −1 for atropine and scopolamine, respectively. The extraction recovery was at least 80%, and the intra- and inter-day precision (relative standard deviation) were below 15% at 1, 5, and 50 µg kg −1 atropine and scopolamine spiked levels. The validation parameters showed that the method was fit for the purpose of accurate LC-MS/MS quantification of atropine and scopolamine. The SLE with DnS is high-throughput, enabling the extraction of TAs in 2.3 min per sample or at least 60 samples in 140 min. Whereas typical TA extraction methods require lengthy and costly clean-up and concentration steps, the DnS does not require these steps, sophisticated equipment, or an expert operator for execution, which makes it a simpler and straightforward procedure for TA analysis in different grain-based food matrices. Application of the LC-MS/MS method showed that one in 80 millet or corn, 18 in 269 soybeans, 20 in 62 soymeal and 20 in 42 Super Cereals samples had atropine and scopolamine above the maximum level of 1 μg kg −1 set by the EU Commission Regulation. TA contamination in these samples could either be due to the mixing with (visible) or exposure to (invisible) TA-producing plant material. The latter was proven through an exposure experiment, which showed that atropine and scopolamine from Datura stramonium seeds can be transferred to food grains (soybeans) invisibly with prolonged contact.

Tackling temporary names: interim solutions for the taxonomic impediment - Tammy Horton; Muriel Rabone; Shane T. Ahyong; Rüdiger Bieler; Christopher B. Boyko; Simone N. Brandão; Gustav Paulay; Erik Simon-Lledó; Ben Boydens; Wim Decock; Stefanie Dekeyzer; Lynn Delgat; et al. (Marine Biodiversity, 2025)
Against a background of the climate and biodiversity crises, there is an urgent need for robust and citable biodiversity information for policy and management decisions. Species are fundamental units of biodiversity and underpin communication in biology. Delineating, describing, and naming species provide the foundation for tracking biodiversity. Taxonomists recognise over 2 million described species, the scientific names of which follow provisions of codes of nomenclature, providing stability for communication about biodiversity. However, described species represent only a fraction of global biodiversity. Current advances in the fields of molecular biology and the growing use of image-based identifications have resulted in an explosion of informal species names globally, herein referred to as temporary names, increasing the rate of discovery of undescribed species and cryptic species complexes. We define two categories of temporary names: Type 1 names that are delineated in a local context but not further assessed; and Type 2 names that have been taxonomically assessed and recognised as either new or part of an unresolved species complex. We explore the different types and uses of temporary names, indicate how they can be managed in a robust and standardised manner and demonstrate how biodiversity databases, such as WoRMS, can be expanded to allow the tracking of both formal and informal scientific names. We propose a solution for the expanding problem of temporary names by defining and recommending the addition of Type 2 temporary names to nomenclatural databases such as WoRMS. We provide practical recommendations on how such names should be selected for entry and then entered to databases in a standardised way. These recommendations are a small step forward, but their broad adoption would support the robust integration of informal and formal taxonomies.

Investigating the effect of protein type and protein concentration on texture and mouthfeel sensory properties of plant and animal-based beverages - Min Sung Kim; Laura Nattress; Christopher T. Simons (Food Quality and Preference, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

The temperature dependence of greenhouse gas production from Central African savannah soils - Nicholas T. Girkin; Hannah V. Cooper; Alice S. Johnston; Martha Ledger; G.R. Mouanda Niamba; Christopher H. Vane; Vicky Moss-Hayes; Dafydd Crabtree; Greta C. Dargie; Saul Vasquez; Yannick Bocko; Emmanuel Mampouya Wenina; et al. (Geoderma Regional, 2025)

Legume protein gelation: The mechanism behind the formation of homogeneous and fractal gels - Alice Y.J. Tiong; Simon Crawford; Liliana de Campo; Vasyl Ryukhtin; Christopher J. Garvey; Warren Batchelor; Leonie van ’t Hag (Food Hydrocolloids, 2025)

Lineage diversity in a Melanesian lizard radiation (Gekkonidae: Nactus) further highlights exceptional diversity and endemism in eastern Papua New Guinea - Paul M. Oliver; Fred Kraus; Christopher C. Austin; Leonardo G. Tedeschi; Aurora R. O’Brien; Simon T. Maddock (Organisms Diversity & Evolution, 2024)
New Guinea and surrounding islands are home to some of the richest assemblages of insular biodiversity in the world. The key geological drivers of species richness in this region are largely considered to be mountain uplift and development of offshore archipelagos—some of which have accreted onto New Guinea—with the role of mountain uplift and elevational gradients receiving more attention than the role of isolation on islands. Here, we examine the distribution of lineage richness and body-size diversity in a radiation of Melanesian lizards that is almost entirely absent from montane habitats but closely associated with islands—the geckos of the genus Nactus . Our data indicate that eastern New Guinea—centred on the East Papuan Composite Terrane (EPCT)—shows particularly high levels of endemism and body-size diversity and is also inferred to be a source area for multiple independent colonisations elsewhere in New Guinea, the Pacific and Australia. Two Nactus lineages in Australia have closest relatives occurring to the north of New Guinea’s Central Cordillera, suggesting dispersal through this area in the mid-Miocene, possibly via seaways that would have isolated the islands to the east and west of the proto-Papuan region. Syntopic species tend to differ in body length; however, at a phylogenetic scale, this trait appears to be conservative, with small-sized and large-sized species clustered into separate lineages. These data suggest that species richness in Melanesian Nactus is in part explained by morphological diversification enabling the presence of sympatric communities to exist, but to a greater extent by multiple instances of dispersal and extensive allopatric and parapatric speciation, especially in and around the islands of the EPCT.

Feedback control of apple juice quality during storage via multiple, mild in-situ processing treatments - Jin Hong Mok; Taras Pyatkovskyy; Brian Heskitt; Ashley Soldavini; Christopher T. Simons; Ahmed Yousef; Sudhir K. Sastry (Journal of Food Engineering, 2024)

“That Looks Like My Kitchen!” − Personalized context by usage frequency and familiarity influences consumer perception and liking of chicken nuggets in VR - Kym Man; Jeremy A. Patterson; Christopher T. Simons (Food Research International, 2024)

Ulvans are not equal - Linkage and substitution patterns in ulvan polysaccharides differ with Ulva morphology - Joel T. Kidgell; Christopher R.K. Glasson; Marie Magnusson; Ian M. Sims; Simon F.R. Hinkley; Rocky de Nys; Susan M. Carnachan (Carbohydrate Polymers, 2024)

Fingerprinting black tea: When spectroscopy meets machine learning a novel workflow for geographical origin identification - Yicong Li; Natasha Logan; Brian Quinn; Yunhe Hong; Nicholas Birse; Hao Zhu; Simon Haughey; Christopher T. Elliott; Di Wu (Food Chemistry, 2024)

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Optimising mechanical separation of anaerobic digestate for total solids and nutrient removal - Ashley Cathcart; Beatrice M. Smyth; Gary Lyons; Simon T. Murray; David Rooney; Christopher R. Johnston (Journal of Environmental Management, 2023)

A Ceratopteris EXCESS MICROSPOROCYTES1 suppresses reproductive transition in the fern vegetative leaves - Kelley A. Withers; Kevin Falls; Christopher E. Youngstrom; Tommy Nguyen; Anika DeWald; Rebekah M. Yarvis; Gabriel P. Simons; Robert Flanagan; Linh T. Bui; Erin E. Irish; Chi-Lien Cheng (Plant Science, 2023)

Characterization of the impact of chlorogenic acids on tactile perception in coffee through an inverse effect on mouthcoating sensation - Brianne M. Linne; Edisson Tello; Christopher T. Simons; Devin G. Peterson (Food Research International, 2023)

Reducing the time-dependent climate impact of intensive agriculture with strategically positioned short rotation coppice willow - David Livingstone; Beatrice M. Smyth; Rachel Cassidy; Simon T. Murray; Gary A. Lyons; Aoife M. Foley; Christopher R. Johnston (Journal of Cleaner Production, 2023)

Identifying Gaps and Challenges in Global Pesticide Legislation that Impact the Protection of Consumer Health: Rice as a Case Study - Patricia Kubiak-Hardiman; Simon A. Haughey; Julie Meneely; Sarah Miller; Kaushik Banerjee; Christopher T. Elliott (Exposure and Health, 2023)
With continued global population expansion, food production will have to increase with crops protected against the growing menace of pests, requiring the increased use of pesticides globally to ensure that agricultural production is optimised and remains economically viable. The aim of this systematic review was to perform an in-depth analysis of pesticide legislation, focusing on rice, to understand the gaps that exist in the harmonisation across different countries. Tricyclazole, carbendazim, thiamethoxam and acephate were considered as these received the highest numbers of RASFF notifications and alerts due to their presence in rice. Global differences in regulations cause trade issues, especially when developing countries use unauthorised pesticides or different MRLs. Discrepancies in the registration and regulation of sales were found to be a global problem. Sales of pesticides and resulting residues in developing countries that are banned in the EU or US is highly concerning. Evidence suggests farmers’ education regarding pesticide use and protection must be increased, particularly as climate change is impacting pesticide use patterns and their bio-efficacy. In conclusion, international pesticide regulations have been implemented to protect consumer health, the environment and facilitate international trade. However, the absence of national MRLs in some countries or non-alignments with Codex MRLs raise significant concerns regarding some pesticides in relation to the protection of consumer health and the use of mixtures versus single pesticides. Additionally, global differences in pesticide regulation highlight problems in trade, especially when developing countries use unauthorised pesticides or when MRLs are not in agreement.

When considering whether to waste food, consumers focus attention on food label dates rather than phrases - Aishwarya Badiger; Talia Katz; Christopher T. Simons; Brian E. Roe (Waste Management, 2023)

The effects of gamification on engagement and response accuracy in discriminatory sensory testing - Jessica Miao; Christopher T. Simons (Food Quality and Preference, 2023)

Risk assessments for the dietary intake aflatoxins in food: A systematic review (2016–2022) - Kiran Bhardwaj; Julie P. Meneely; Simon A. Haughey; Moira Dean; Patrick Wall; Guangtao Zhang; Bob Baker; Christopher T. Elliott (Food Control, 2023)

The Challenge of Global Aflatoxins Legislation with a Focus on Peanuts and Peanut Products: A Systematic Review - Julie P. Meneely; Oluwatobi Kolawole; Simon A. Haughey; Sarah J. Miller; Rudolf Krska; Christopher T. Elliott (Exposure and Health, 2023)
Globally, of all mycotoxins, aflatoxins present a significant threat to human and animal health and has resulted in the introduction of strict food regulatory limits to protect public health. A systematic review, was performed to elucidate the rationale applied in establishing aflatoxin standards and evaluate the economic impacts of these. The focus was peanuts, a principal trading commodity susceptible to aflatoxin contamination. Results revealed that although regulations are established in many countries, there is huge disparity in the maximum limits applied due to different methodologies used when considering exposure assessment. Moreover, in countries most affected by aflatoxin contamination in peanuts, few, if any standards exist. In the case of risk assessments, knowledge gaps identified include the impact of climate change on peanut aflatoxin contamination, the role of aflatoxins in child stunting, Kwashiorkor and immunomodulation and a lack of occurrence and exposure data in many developing countries from contaminated peanuts. Few quantitative studies evaluating the impact of aflatoxin regulations on trade exist and evidence is lacking in terms of what happens to exports that do not meet regulatory requirements. Evidence does suggest a lack of knowledge of the extent of the aflatoxin problem, associated health risks and mitigation strategies in developing countries. A hugely important factor that needs to be highlighted is that while there is a fundamental right for sufficient, safe, nutritious food, in many cases in low-income and lower middle-income countries there exists an incredibly difficult and complex trade-off between food security and food safety.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Production pathways for profitability and valuing ecosystem services for willow coppice in intensive agricultural applications - David Livingstone; Beatrice M. Smyth; Erin Sherry; Simon T. Murray; Aoife M. Foley; Gary A. Lyons; Christopher R. Johnston (Sustainable Production and Consumption, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Increased yield and CO 2 sequestration potential with the C 4 cereal Sorghum bicolor cultivated in basaltic rock dust‐amended agricultural soil - Mike E. Kelland; Peter W. Wade; Amy L. Lewis; Lyla L. Taylor; Binoy Sarkar; M. Grace Andrews; Mark R. Lomas; T. E. Anne Cotton; Simon J. Kemp; Rachael H. James; Christopher R. Pearce; Sue E. Hartley; et al. (Global Change Biology, 2020)
Land‐based enhanced rock weathering (ERW) is a biogeochemical carbon dioxide removal (CDR) strategy aiming to accelerate natural geological processes of carbon sequestration through application of crushed silicate rocks, such as basalt, to croplands and forested landscapes. However, the efficacy of the approach when undertaken with basalt, and its potential co‐benefits for agriculture, require experimental and field evaluation. Here we report that amending a UK clay‐loam agricultural soil with a high loading (10 kg/m 2 ) of relatively coarse‐grained crushed basalt significantly increased the yield (21 ± 9.4%, SE ) of the important C 4 cereal Sorghum bicolor under controlled environmental conditions, without accumulation of potentially toxic trace elements in the seeds. Yield increases resulted from the basalt treatment after 120 days without P‐ and K‐fertilizer addition. Shoot silicon concentrations also increased significantly (26 ± 5.4%, SE ), with potential benefits for crop resistance to biotic and abiotic stress. Elemental budgets indicate substantial release of base cations important for inorganic carbon removal and their accumulation mainly in the soil exchangeable pools. Geochemical reactive transport modelling, constrained by elemental budgets, indicated CO 2 sequestration rates of 2–4 t CO 2 /ha, 1–5 years after a single application of basaltic rock dust, including via newly formed soil carbonate minerals whose long‐term fate requires assessment through field trials. This represents an approximately fourfold increase in carbon capture compared to control plant–soil systems without basalt. Our results build support for ERW deployment as a CDR technique compatible with spreading basalt powder on acidic loamy soils common across millions of hectares of western European and North American agriculture.

Feeding Whole Thraustochytrid Biomass to Cultured Atlantic Salmon (Salmo salar) Fingerlings: Culture Performance and Fatty Acid Incorporation - Kim Jye Lee Chang; Christopher C. Parrish; Cedric J. Simon; Andrew T. Revill; Peter D. Nichols (Journal of Marine Science and Engineering, 2020)
Replacement of fish oil by 5% thraustochytrid whole cell biomass in diets for Atlantic salmon had no ill effect on fish growth performance, carcass total lipid and total fatty acid content. Carcass fatty acid composition indicated incorporation of the dietary thraustochytrid-derived fatty acids. This was confirmed by compound specific stable isotope analysis (CSIA) which revealed significantly 13C-depleted (δ13C value of −24‰) ω3 long-chain (≥C20) polyunsaturated fatty acids (ω3 LC-PUFAs) in the fingerlings fed the thraustochytrid biomass containing diet, reflecting the highly 13C-depleted glycerol used to grow the thraustochytrid cultures. This finding demonstrates the bioavailability of the ω3 LC-PUFA of the Australian strain thraustochytrid culture (TC) 20 from the whole cell biomass that was partly cultivated on crude glycerol produced during biodiesel manufacturing. This paper demonstrates the value of Australian thraustochytrid strains grown heterotrophically for their wider biotechnological potential including as a source of higher value lipids, in particular the health-benefitting ω3 LC-PUFA, for use in aquaculture and other applications.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Quantifying trends and uncertainty in prehistoric forest composition in the upper Midwestern United States - Andria Dawson; Christopher J. Paciorek; Simon J. Goring; Stephen T. Jackson; Jason S. McLachlan; John W. Williams (Ecology, 2019)
Forest ecosystems in eastern North America have been in flux for the last several thousand years, well before Euro‐American land clearance and the 20th‐century onset of anthropogenic climate change. However, the magnitude and uncertainty of prehistoric vegetation change have been difficult to quantify because of the multiple ecological, dispersal, and sedimentary processes that govern the relationship between forest composition and fossil pollen assemblages. Here we extend STEPPS, a Bayesian hierarchical spatiotemporal pollen–vegetation model, to estimate changes in forest composition in the upper Midwestern United States from about 2,100 to 300 yr ago. Using this approach, we find evidence for large changes in the relative abundance of some species, and significant changes in community composition. However, these changes took place against a regional background of changes that were small in magnitude or not statistically significant, suggesting complexity in the spatiotemporal patterns of forest dynamics. The single largest change is the infilling of Tsuga canadensis in northern Wisconsin over the past 2,000 yr. Despite range infilling, the range limit of T. canadensis was largely stable, with modest expansion westward. The regional ecotone between temperate hardwood forests and northern mixed hardwood/conifer forests shifted southwestward by 15–20 km in Minnesota and northwestern Wisconsin. Fraxinus , Ulmus , and other mesic hardwoods expanded in the Big Woods region of southern Minnesota. The increasing density of paleoecological data networks and advances in statistical modeling approaches now enables the confident detection of subtle but significant changes in forest composition over the last 2,000 yr.

Island questions: the chronology of the Brochtorff Circle at Xagħra, Gozo, and its significance for the Neolithic sequence on Malta - Caroline Malone; Nathaniel Cutajar; T. Rowan McLaughlin; Bernardette Mercieca-Spiteri; Anthony Pace; Ronika K. Power; Simon Stoddart; Sharon Sultana; Christopher Bronk Ramsey; Elaine Dunbar; Alex Bayliss; Frances Healy; et al. (Archaeological and Anthropological Sciences, 2019)

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

How ecology shapes exploitation: a framework to predict the behavioural response of human and animal foragers along exploration–exploitation trade‐offs - Christopher T. Monk; Matthieu Barbier; Pawel Romanczuk; James R. Watson; Josep Alós; Shinnosuke Nakayama; Daniel I. Rubenstein; Simon A. Levin; Robert Arlinghaus (Ecology Letters, 2018)
Understanding how humans and other animals behave in response to changes in their environments is vital for predicting population dynamics and the trajectory of coupled social‐ecological systems. Here, we present a novel framework for identifying emergent social behaviours in foragers (including humans engaged in fishing or hunting) in predator–prey contexts based on the exploration difficulty and exploitation potential of a renewable natural resource. A qualitative framework is introduced that predicts when foragers should behave territorially, search collectively, act independently or switch among these states. To validate it, we derived quantitative predictions from two models of different structure: a generic mathematical model, and a lattice‐based evolutionary model emphasising exploitation and exclusion costs. These models independently identified that the exploration difficulty and exploitation potential of the natural resource controls the social behaviour of resource exploiters. Our theoretical predictions were finally compared to a diverse set of empirical cases focusing on fisheries and aquatic organisms across a range of taxa, substantiating the framework's predictions. Understanding social behaviour for given social‐ecological characteristics has important implications, particularly for the design of governance structures and regulations to move exploited systems, such as fisheries, towards sustainability. Our framework provides concrete steps in this direction.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Lingual tactile sensitivity: effect of age group, sex, and fungiform papillae density - Ronald G. Bangcuyo; Christopher T. Simons (Experimental Brain Research, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Estrogen-related genes and their contribution to racial differences in breast cancer risk - Kerryn W. Reding; Chu Chen; Kimberly Lowe; David R. Doody; Christopher S. Carlson; Christina T. Chen; John Houck; Linda K. Weiss; Polly A. Marchbanks; Leslie Bernstein; Robert Spirtas; Jill A. McDonald; et al. (Cancer Causes & Control, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Temporal and vertical variations of lipid biomarkers during a bottom ice diatom bloom in the Canadian Beaufort Sea: further evidence for the use of the IP25 biomarker as a proxy for spring Arctic sea ice - Thomas A. Brown; Simon T. Belt; Benoît Philippe; Christopher J. Mundy; Guillaume Massé; Michel Poulin; Michel Gosselin (Polar Biology, 2011)

Reply to Comment: Holocene palaeoceanographic changes in Barrow Strait, Canadian Arctic: foraminiferal evidence. T. R. Gregory, C. W. Smart, M. B. Hart, G. Massé, L. L. Vare and S. T. Belt (2010). Journal of Quaternary Science 25 : 903–910 - Thomas R. Gregory; Christopher W. Smart; Malcolm B. Hart; Guillaume Massé; Lindsay L. Vare; Simon T. Belt (Journal of Quaternary Science, 2010)

Holocene palaeoceanographic changes in Barrow Strait, Canadian Arctic: foraminiferal evidence - Thomas R. Gregory; Christopher W. Smart; Malcolm B. Hart; Guillaume Massé; Lindsay L. Vare; Simon T. Belt (Journal of Quaternary Science, 2010)
Holocene changes in the benthic and planktic foraminiferal fauna (>63 µm) from a marine sediment core (ARC‐3 Canadian Arctic Archipelago, 74° 16.050′ N, 91° 06.380′ W, water depth 347 m) show that significant environmental and palaeoceanographic variations occurred during the last 10 ka. Foraminiferal assemblages are restricted to the ca. 4.5–10 ka interval as younger samples are mostly barren of foraminifera due to intense carbonate dissolution after ca. 4.5 ka. Foraminiferal assemblages in the ca. 4.5–10 ka interval are dominated by the benthic species Islandiella helenae and Cassidulina reniforme (57% of total), with Elphidium clavatum , Cibicides lobatulus and Buccella frigida also being common in this interval. The dominance of these species indicates a seasonal sea ice regime which is consistent with the occurrence of the sea ice diatom‐derived organic geochemical biomarker IP 25 throughout the core. The abundances of C. reniforme and E. clavatum decline upcore; consistent with more frequent mixing of the Barrow Strait water column during the early Holocene. It is likely that the influence of CO 2 ‐rich Arctic surface water masses have caused an increase in bottom water corrosivity after ca. 8.5 ka, and dissolution has been further enhanced by sea ice‐related processes after ca. 6 ka, concomitant with increased IP 25 fluxes. Dissolution is strongest when IP 25 fluxes are highest, suggesting a link between the sea ice and benthic systems. Copyright © 2010 John Wiley & Sons, Ltd.

Rewarding and unrewarding aspects of deployment to Iraq and its association with psychological health in UK military personnel - Josefin Sundin; Nicola T. Fear; Lisa Hull; Norman Jones; Christopher Dandeker; Matthew Hotopf; Simon Wessely; Roberto J. Rona (International Archives of Occupational and Environmental Health, 2010)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Self-selected exercise intensity during household/garden activities and walking in 55 to 65-year-old females - Robert T. Withers; Anthony G. Brooks; Simon M. Gunn; John L. Plummer; Christopher J. Gore; John Cormack (European Journal of Applied Physiology, 2006)

The energy cost of household and garden activities in 55- to 65-year-old males - Simon M. Gunn; Anthony G. Brooks; Robert T. Withers; Christopher J. Gore; John L. Plummer; John Cormack (European Journal of Applied Physiology, 2005)

Measurement and prediction of energy expenditure in males during household and garden tasks - Simon M. Gunn; Grant E. van der Ploeg; Robert T. Withers; Christopher J. Gore; Neville Owen; Adrian E. Bauman; John Cormack (European Journal of Applied Physiology, 2004)

Measurement and prediction of energy expenditure in males during household and garden tasks - Simon M. Gunn; Grant E. van der Ploeg; Robert T. Withers; Christopher J. Gore; Neville Owen; Adrian E. Bauman; John Cormack (European Journal of Applied Physiology, 2004)

The effect of modified atmospheres on the survival of the eggs of four storage mite species - Simon T. Conyers; Christopher H. Bell (Experimental and Applied Acarology, 2003)

c-fos induction in rat superficial dorsal horn following cutaneous application of noxious chemical or mechanical stimuli - Steven L. Jinks; Christopher T. Simons; Jean-Marc Dessirier; Mirela Iodi Carstens; Joseph F. Antognini; E. Carstens (Experimental Brain Research, 2002)

Role of neuronal nicotinic-acetylcholine receptors in the activation of neurons in trigeminal subnucleus caudalis by nicotine delivered to the oral mucosa - E. Carstens; Christopher T. Simons; Jean-Marc Dessirier; M. Iodi Carstens; Steven L. Jinks (Experimental Brain Research, 2000)